Characterization and cadmium detoxification dynamics of endophytic bacteria, isolated from rice plants - Irfan Haider; Ihsan Ullah; Sajjad Ullah Khan; Iqbal Munir; Aisha Mateen; Naser AL-Kenani; Bassam Oudh Al Johny; Yasir Anwar; Habeeb M. Al-Solami; Torki M. Alahmadi; Nadiah Alsulami; Ali Zari; et al. (Journal of King Saud University: Science, 2022)
Over the past few decades, a special focus has been placed on plant endophytic bacteria's ability to improve plant responses to various stresses. We isolated bacteria from SWAT-1 rice variety and characterized them biochemically and morphologically. The isolates included seven from leaves, eight from roots, and five from stems. A total of 20 isolates were identified, of which four were gram-negative and sixteen were gram-positive. Eight of the isolates were catalase-positive, whereas twelve were catalase-negative. The highest production of indole-3-acetic acid (IAA) was recorded in IALIV (4.01 µg/ml), with the lowest production by IARIV (0.22 µg/ml). Similarly, IALIII and IASII produced the lowest (0.24 µg/ml) and highest (0.73 µg/ml) amylase respectively. IARVI and IASII showed maximum antimicrobial activity (27 mm) against Calcibacter and minimum activity (10 mm) against Xanthomonas. In terms of growth promotion, all isolates increased shoot length, root length, biomass production, and Cd uptake in plants. As compared to uninoculated plants, the inoculation of endophytes significantly improved (p < 0.05) the plant growth attributes in plants exposed to Cd stressors (7 mM and 12 mM). Generally, isolates have been shown to be useful as biocontrol agents and biofertilizers.